Advancements in Magnetic Resonance in Porous Media - Bowers, Clifford R.; Vasenkov, Sergey (Diffusion Fundamentals, 2019)
This is a brief summary of the Fourteenth International Bologna Conference on Magnetic Resonance in Porous Media (MRPM14).